2007
DOI: 10.1016/j.bone.2007.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Bone mass is inversely proportional to Dkk1 levels in mice

Abstract: The Wnt/β-catenin signaling pathway has emerged as a key regulator in bone development and bone homeostasis. Loss-of-function mutations in the Wnt co-receptor LRP5 result in osteoporosis and "activating" mutations in LRP5 result in high bone mass. Dickkopf-1 (DKK1) is a secreted Wnt inhibitor that binds LRP5 and LRP6 during embryonic development, therefore it is expected that a decrease in DKK1 will result in an increase in Wnt activity and a high bone mass phenotype. Dkk1 −/− knockout mice are embryonic letha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(111 citation statements)
references
References 56 publications
2
108
0
1
Order By: Relevance
“…Interestingly, for one particular LRP5 gain-of-function mutation, G171V, decreased inhibition of LRP5 by Dkk1 was suggested to account for increased LRP5 signaling (Boyden et al 2002;Ai et al 2005). Similar to humans, heterozygous Dkk1 þ/2 mice show an increase in bone mineral density (Morvan et al 2006;MacDonald et al 2007). Conversely, transgenic mice overexpressing Dkk1 in bone develop osteopenia (Li et al 2006), suggesting that Dkk1 antagonizes Wnt -LRP5 signaling to regulate physiological levels of bone mass.…”
Section: Role Of Dkks In Embryonic Development and Diseasementioning
confidence: 99%
“…Interestingly, for one particular LRP5 gain-of-function mutation, G171V, decreased inhibition of LRP5 by Dkk1 was suggested to account for increased LRP5 signaling (Boyden et al 2002;Ai et al 2005). Similar to humans, heterozygous Dkk1 þ/2 mice show an increase in bone mineral density (Morvan et al 2006;MacDonald et al 2007). Conversely, transgenic mice overexpressing Dkk1 in bone develop osteopenia (Li et al 2006), suggesting that Dkk1 antagonizes Wnt -LRP5 signaling to regulate physiological levels of bone mass.…”
Section: Role Of Dkks In Embryonic Development and Diseasementioning
confidence: 99%
“…Skeletal trauma causes a local increase in Wnt signaling [11] and it has been shown that the pathways involved in bone Wnt signaling are necessary for bone healing [11][12] and for bone formation in general [13][14][15]. Fracture repair can be influenced by blocking Dkk1 in mice [16] and a decrease in Dkk1 gene expression leads to an increase in bone mass and strength [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…One such example is Dickkopf-1 (Dkk1), which inhibits Wnt signaling by binding to LRP6 (9,11,12). Dkk1 has been shown to play a crucial role in bone formation, vertebrate embryogenesis, and suppression of cancer cell proliferation (13)(14)(15). Therefore, Wnt ligands, receptors Fz and LRP, and their natural inhibitors are all of great therapeutic interest.…”
mentioning
confidence: 99%